2011
DOI: 10.1038/npre.2011.6509.1
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effects of a Synthetic Aluminium-Magnesium Silicate on Avian Influenza Virus

Abstract: Effects of a synthetic Aluminium-Magnesium Silicate [AMS] on Avian Influenza Virus (AIV) were tested. Equal amounts of H 5 N 1 AIV samples and of AMS were mixed, left one hour, at room teperature before centrifuging. The supernatants were remeasured and tested for viral titre, for Mean Death Time (MDT) and Embryo Mortality Rate (EMR) of chicken eggs. Volumes of the viral samples reduced at rate of 23.4 ± 5.48 %. Viral titres reduced significantly (P from HA, 73 ± 32.72 to 1.4 ±0.43. Also, mortality of infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…HIV titers of five other samples, also increased (P = 0.009) from a mean of 4.00 ± 1.63 to 14.00 ± 2.00 when treated with the Antivirt ® once. When treatment with the Antivirt ® was repeated, mean of the plasma-HIV titers reduced significantly (P = 0.024) from 14.00 ± 2.00 to 6.50 ± 1.50 [14]. The initial increase in viral loads and subsequent reductions reported by NIMR in this clinical trial is exact repeat of results of that in vitro study.…”
Section: Discussionsupporting
confidence: 66%
“…HIV titers of five other samples, also increased (P = 0.009) from a mean of 4.00 ± 1.63 to 14.00 ± 2.00 when treated with the Antivirt ® once. When treatment with the Antivirt ® was repeated, mean of the plasma-HIV titers reduced significantly (P = 0.024) from 14.00 ± 2.00 to 6.50 ± 1.50 [14]. The initial increase in viral loads and subsequent reductions reported by NIMR in this clinical trial is exact repeat of results of that in vitro study.…”
Section: Discussionsupporting
confidence: 66%
“…The AMS showed a highly negative charge due to the silicate molecules and it easily binds to amine group of the drug molecules and it facilitates the prolonged release of the drug. Recently, Ezeibe et al ., [13] reported that the AMS is highly effective against Fowl Pox Virus, New Castle Disease virus [14], Avian Influenza virus [15], Parvovirus [16], Infectious Bursal disease virus [17] and Antiplasmodial effects. In this study, the oral beads were developed to treat the chicken coccidiosis infection using green tea/AMS hybrid material.…”
Section: Introductionmentioning
confidence: 99%
“…Canine parvovirus (CPV) is widely distributed in the global canine population and remains an important cause of morbidity and mortality in this species [4,5]. There are two common clinical forms: gastro-enteritis form common in adults and myocarditis form common in puppies [6]. The disease is characterized by lethargy, leucopenia, dehydration, anorexia, fever, vomiting and diarrhoea, which may contain mucus or blood with a very strong foul smell [7,2,8].…”
Section: Introductionmentioning
confidence: 99%